Pengolahan Limbah Cair Rumah Makan Dengan Constructed Wetlands Skala Rumah Tangga - Ananta, Muhammad Andre; Suciana, Indah; Izwara, Yarra; Apriani, Isna (Universitas Tanjungpura, 2024)
Wastewater from restaurants has a high organic content. Wastewater must be processed until it conforms with the effluent standard before being disposed of in water. Construction of subsurface wetland is one of the treatment options. This study made use of a reactor that Kiambang and Melati Air had planted. Sedimentation basin, wetland basin, and treatment basin are the three reservoirs used in this study. The wastewater was a sedimented effluent from restaurant operations. Seeding, acclimation, and running are the processes used. running for seven days. The variables under test were pH, TSS, and BOD (biological oxygen demand). Before treatment, the concentration is BOD 546,75 mg/l, TSS 340 mg/l, and pH 7,24. After treatment, the concentration is BOD 30,75 mg/l, TSS 95 mg/l, and pH 7,42. As a result, BOD has an efficiency of 94,376% and TSS has an efficiency of 72%. The concentrations of TSS did not meet the set quality criteria, although the levels of BOD and pH did.